Peran Tokoh Adat dalam Sistem Sosial dan Budaya Tolaki di Tengah Tantangan Globalisasi - Koimah, Siti Mariyatul; Salam, Fitrah Febri; Zahra, Nur Amalia (Jurnal Ilmu Sosial dan Budaya Indonesia, 2025)
This study aims to examine the structure of customary leadership and the social roles of traditional leaders within the Tolaki ethnic group, as well as how these customary values are understood and practiced by the younger generation. The Sara system, as the customary law of the Tolaki people, plays a significant role in regulating social, cultural, and religious life. Traditional leaders such as Toono Sara, Meantu’u, Pabitara, and Tolea have strategic functions in maintaining social order and resolving conflicts through customary means. However, challenges have emerged due to changing times, where the younger generation tends to view these traditions merely as ceremonial practices, lacking deeper philosophical understanding. This study uses a literature review method, analyzing relevant scholarly articles, books, and research reports. The findings show that Sara not only has local significance but also contains universal values such as justice, deliberation, and social harmony. To sustain its relevance, synergy is needed among traditional leaders, youth, academics, and local governments to develop educational and participatory approaches that contextualize these values in modern life. This study contributes to the development of social and cultural studies and to the preservation of local wisdom amid modernization.